A Review of Discharge Medications in Patients Admitted with Acute Decompesated Heart Failure in a Tertiary Referral Centre - Chung, B.K.; Ling, H.S.; Chua, P.F.; Fong, A.Y.Y. (Elsevier, 2019)
Background: National guidelines for heart failure recommend prescription of certain classes of drugs to improve prognosis in patients admitted with acute decompensated heart failure (ADHF). It has been noted during clinical follow up such patients are discharged with different treatment regimes.